Tissue engineering for Tracheal replacement: strategies and challenges - Abdul Samat, Asmak; Yahaya, Badrul Hisham; Abdul Hamid, Zuratul Ain; Jaafar, Mariatti (Springer Nature Switzerland AG, 2022)
The critical feature in trachea replacement is to provide a hollow cylindrical framework that is laterally stable and longitudinally flexible, facilitating cartilage and epithelial tissue formation. Despite advanced techniques and sources of materials used, most inherent challenges are related to the complexity of its anatomy. Limited blood supply leads to insufficient regenerative capacity for cartilage and epithelium. Natural and synthetic scaffolds, different types of cells, and growth factors are part of tissue engineering approaches with varying outcomes. Pre-vascularization remains one of the crucial factors to expedite the regenerative process in tracheal reconstruction. This review discusses the challenges and strategies used in tracheal tissue engineering, focusing on scaffold implantation in clinical and preclinical studies conducted in recent decades.